Parametric Analysis of New Assembled Double Steel Plate-Concrete Composite Shear Wall Structure. Issue 2 (April 2021) - Hong, Cheng; Yi, Shuai; Zhang, Baohua; Liu, Kai; Xu, Qiuhua
Abstract: At present, China's construction industry is developing rapidly towards the goal of "design standardization and industrial production". The State Council and local governments have also issued relevant documents on the development of fabricated steel structures, the development of assembled steel structure in China has been promoted. The Shear Wall structure is one of the most important components to ensure the earthquake resistance of the whole building, which can obviously improve the overall anti-lateral stiffness of the building, so it is widely used in high-rise buildings. In this paper, the thickness of steel plate and the distance between studs are selected as the parameters of the new shear wall structure, and 9 groups of models are used for parametric analysis. Finally, the data are compared and corresponding conclusions are drawn.